Intrasylvian Retraction Technique to Facilitate the Sylvian Fissure Dissection: A Clinical Study of 125 Cases - Sriamornrattanakul, Kitiporn; Ariyaprakai, Chanon (Asian Journal of Neurosurgery, 2024)
Although many authors have recommended the retractorless technique to avoid retractor-induced brain injury, others usually use brain retractors with a meticulous technique to facilitate the surgery, especially for sylvian fissure dissection. The intrasylvian retraction technique was described for sylvian fissure opening, but no clinical evidence was found. We evaluate the efficacy and safety of this technique for the distal transsylvian approach. We reviewed the video records of clinical cases where the distal transsylvian approach was performed using the intrasylvian retraction technique for aneurysm treatment and middle cerebral artery (MCA) bypass between September 2018 and August 2022. Operative techniques are described. The efficacy and safety of the technique were assessed by full exposure of the sylvian fissure and new postoperative perisylvian hematoma, respectively. One hundred twenty-five cases were included and had an average age of 53.5 (range 16–85) years. Women comprised 73.6%. Aneurysm surgery, pure MCA revascularization, and aneurysm surgery with MCA revascularization were 106 (84.8%), 12 (9.6%), and 7 cases (5.6%), respectively. The most common aneurysm location was the internal carotid artery-posterior communicating artery junction in 37 cases (34.9%), followed by the anterior communicating artery in 27 (25.5%). Full exposure of the Sylvian fissure was achieved in all cases. No perisylvian hematoma was detected by immediate postoperative computed tomography in any patient. Using an appropriate technique for brain retractor application, sylvian fissure dissection was safely performed. The intrasylvian retraction technique effectively facilitated sylvian fissure dissection and provided wide exposure for the distal transsylvian approach.
Keywords: brain retractor; distal transsylvian approach; intrasylvian retraction; sylvian fissure dissection; sylvian fissure split